Macacine alphaherpesvirus 1 (B Virus) Infection in Humans, Japan, 2019 - Souichi Yamada; Harutaka Katano; Yuko Sato; Tadaki Suzuki; Akihiko Uda; Keita Ishijima; Motoi Suzuki; Daigo Yamada; Shizuko Harada; Hitomi Kinoshita; Phu Hoang Anh Nguyen; Hideki Ebihara; et al. (Emerging Infectious Diseases, 2024)
Two human patients with Macacine alphaherpesvirus 1 infection were identified in Japan in 2019. Both patients had worked at the same company, which had a macaque facility. The rhesus-genotype B virus genome was detected in cerebrospinal fluid samples from both patients.